Trends in Antibiotic Resistance in Uropathogens at Mbarara Regional Referral Hospital (2019–2024): A Retrospective Study - Bazira J; Pauline Petra N; Nakato CN; Walekhwa AW; Nakazibwe B; Kawuma S (Infection and Drug Resistance)
Joel Bazira,1 Nalumaga Pauline Petra,1 Constance Nakimuli Nakato,1 Abel W Walekhwa,2,3 Brenda Nakazibwe,3 Simon Kawuma4 1Department of Microbiology, Mbarara University of Science and Technology, Mbarara, Uganda; 2Science, Technology, Innovation Secretariat, Office of the President, Kampala, Uganda; 3IDEMU Mathematical Modeling Unit, Kampala, Uganda; 4Department of Computer Science, Faculty of Science, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Joel Bazira, Email jbazira@must.ac.ugBackground: Urinary tract infections (UTIs) are among the most common bacterial infections globally, with significant morbidity and rising antimicrobial resistance (AMR). This study aimed to investigate the prevalence of uropathogens and their antimicrobial resistance patterns at Mbarara Regional Referral Hospital (MRRH) in Uganda.Methods: A retrospective analysis of 939 urine culture- positive records from January 2019 to December 2024 was conducted. Isolates were identified, and antimicrobial susceptibility testing was performed using the disc diffusion method. Data on patient demographics, uropathogen distribution, and resistance trends of organisms with greater than or equal to 25 isolates were analyzed using Python-based statistical methods, including Chi-square and Mann–Kendall trend analysis.Results: Escherichia coli was the most isolated pathogen, accounting for 428 isolates (45.6%), followed by Klebsiella spp. with 385 isolates (41.0%) while Citrobacter spp. and Enterococcus spp. contributed 42 (4.5%) and 26 (2.8%) isolates, respectively. The cases were dominated by females (69.0%). There was an extremely high resistance to commonly prescribed antibiotics such as ampicillin (91.3%) and sulfamethoxazole (91.6%). Carbapenem resistance was overall low (≤ 10.3%) but also had a statistically significant rising trend in Klebsiella spp. (p = 0.0415). Multidrug resistance (MDR) was present in 56.9% of the isolates, predominantly in Escherichia coli and Klebsiella spp. and 70% of the MDR isolates were ESBL producers.Conclusion: This study underscores the urgent need for routine culture and sensitivity, and updated treatment guidelines to address the rising AMR among uropathogens in Uganda.Keywords: antibiotic resistance, multidrug resistance, urinary tract infections, uropathogens